Zero-dimensional copper-doped bismuth tungstate nano photocatalyst with visible light response, preparation method and method for treating tetracycline sewage
By developing a zero-dimensional copper-doped bismuth tungstate nanophotocatalyst with visible light response, the problem of tetracycline wastewater being difficult to degrade at room temperature is solved, efficient tetracycline degradation is achieved, ensuring the safety and stability of the catalyst, and significantly improving the light Catalytic oxidation reaction rate and carrier separation capability.
Patent Information
- Application Number
- CN202411418859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to efficiently degrade tetracycline sewage under normal temperature and visible light conditions, and the traditional treatment methods are inefficient, the operating conditions are harsh, and the catalyst safety and stability are insufficient.
Develop a zero-dimensional copper-doped bismuth tungstate nanophotocatalyst with visible light response, which is prepared by forming a suspension in ethylene glycol, heated, washed, dried and heat-treated, and dispersed in wastewater. Photocatalytic reaction, degradation of tetracycline.
Under visible light irradiation for 2 hours, the degradation rate of tetracycline can reach 94.5%, and the catalyst remains highly active after 5 cycle tests, which significantly improves the photocatalytic oxidation reaction rate and carrier separation ability.
Smart Images

Figure CN119186581A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment and visible light photocatalysts, and specifically relates to a visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst and a preparation method thereof, and a method for treating tetracycline wastewater. Background Art
[0002] Tetracycline is a class of antibiotics widely used in healthcare and veterinary fields, and its production and use are relatively large in China.
[0003] The pharmaceutical industry is an important source of tetracycline entering the environment. In the production process of drugs such as chlortetracycline, oxytetracycline, doxycycline, and minocycline, a large amount of wastewater containing tetracycline is generated. In addition, tetracycline is used extensively in agriculture and animal husbandry as a feed additive to prevent and treat animal diseases. These drugs enter the environment through animal excrement, especially when animal feces are used as farmland fertilizer, tetracycline will enter the soil and water. In addition, medical waste generated by hospitals and clinics may also become a source of tetracycline pollution if not properly handled. These factors work together to cause tetracycline antibiotics to form a relatively serious pollution problem in water bodies in some areas of my country.
[0004] Once tetracycline antibiotics enter the water body, they will have multiple negative impacts on the aquatic ecosystem. First, acute exposure to high concentrations of tetracycline antibiotics has certain lethal and sublethal effects on aquatic organisms, while long-term exposure to environmental concentrations will affect the growth and development of aquatic organisms and lead to the loss of biodiversity. Secondly, the presence of tetracycline in water bodies may also accumulate through the food chain and ultimately affect human health. More seriously, the presence of antibiotics such as tetracycline may lead to the horizontal transfer of resistance genes between bacteria, increasing the emergence of resistant strains, which poses a huge threat to public health. In addition, tetracycline may also inhibit the growth of beneficial microorganisms in water bodies or soil, change the structure of microbial communities, and thus affect the function of the entire ecosystem.
[0005] The use of photocatalytic technology to degrade tetracycline under natural visible light conditions, thereby reducing biological and environmental risks, is considered a promising strategy. Photocatalytic technology uses specific catalysts to promote the decomposition of organic pollutants such as tetracycline under the action of light, and converts them into harmless small molecules such as carbon dioxide and water. This method has obvious advantages over traditional physical and chemical treatment methods (such as adsorption, precipitation, etc.). First, the photocatalytic process mainly relies on sunlight as an energy source, which not only reduces energy consumption, but also reduces secondary pollution caused by additional energy demand. Secondly, the photocatalytic reaction can be carried out under mild environmental conditions, avoiding harsh conditions such as high temperature and high pressure, making the technology safer and easier to operate. Furthermore, the mild and close-to-nature degradation conditions reduce potential side effects on the ecosystem and provide the possibility of achieving environmentally friendly pollution control.
[0006] Nevertheless, developing photocatalysts that are safe, non-toxic, and stable, and can efficiently degrade tetracycline under room temperature and visible light conditions remains a major technical challenge. Summary of the invention
[0007] In view of the shortcomings of the prior art, the present invention provides a visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst and a preparation method and a method for treating tetracycline wastewater. The purpose of the present invention is to provide a photocatalyst that can efficiently degrade tetracycline under normal temperature and visible light conditions, aiming to solve the problems of low efficiency and harsh operating conditions in traditional treatment methods, while ensuring the safety and stability of the catalyst to achieve effective water purification.
[0008] The first aspect of the present invention is to provide a visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst and a preparation method thereof.
[0009] The preparation method of the photocatalyst comprises the following steps:
[0010] Step S1.1: using tungstate, bismuth salt and copper salt as raw materials, forming a suspension under the stabilization and dispersion effect of ethylene glycol;
[0011] Step S1.2: placing the suspension formed in step S1.1 in a sealed container and heating it to obtain a nano-colloidal substance;
[0012] Step S1.3: washing and drying the nano-colloid formed in step S1.2 to obtain a photocatalyst precursor;
[0013] Step S1.4: heat-treating the photocatalyst precursor obtained in step S1.3 to obtain a visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst.
[0014] As a further optimization scheme, in step S1.1, the tungstate is sodium tungstate, the bismuth salt is bismuth nitrate, and the copper salt is copper chloride.
[0015] As a further optimization scheme, in step S1.1, 5.53 to 5.76 parts by mass of Bi(NO3)3·5H2O, 0.016 to 0.08 parts by mass of CuCl2 and 1.70 to 2.20 parts by mass of Na2WO4·2H2O are added to 22.2 to 33.3 parts by mass of ethylene glycol and mixed to form a suspension.
[0016] As a further optimization scheme, in step S1.2, the suspension formed in step S1.1 is placed in a high-pressure sealed container and reacted at 140-180° C. for 12-15 hours to form a nano-colloid.
[0017] As a further optimization scheme, in step S1.3, the nano-colloid is filtered to separate the solid, which is washed with deionized water and vacuum dried to obtain a photocatalyst precursor.
[0018] As a further optimization scheme, in step S1.4, the precursor is heated to 300±5°C at a heating rate of 5±1°C / min, heated for 2 to 5 hours under this condition, and then cooled to room temperature to obtain the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst.
[0019] By using the above method, a zero-dimensional copper-doped bismuth tungstate nanophotocatalyst responsive to visible light can be prepared.
[0020] The second aspect of the present invention is to provide a method for treating tetracycline wastewater, comprising the following steps:
[0021] Step S2.1: dispersing the above-mentioned visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst in the wastewater containing tetracycline to be treated to obtain a mixed solution;
[0022] Step S2.2: subjecting the mixed solution obtained in step S2.1 to a photocatalytic reaction under visible light irradiation to degrade tetracycline in the sewage;
[0023] Step S2.3: After the reaction is completed, the photocatalyst is separated from the mixed liquid to obtain purified water.
[0024] As a further optimization scheme, in step S2.3, the photocatalyst is recovered from the mixed solution by filtration or centrifugation.
[0025] As a further optimization scheme, in step S2.1, the sewage to be treated contains a variety of organic pollutants including tetracycline; the photocatalyst added to the sewage to be treated is a composite photocatalyst including the above-mentioned visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst.
[0026] Beneficial Effects
[0027] The present invention develops a zero-dimensional (0D) copper atom-doped bismuth tungstate nanomaterial to achieve efficient photocatalytic degradation of tetracycline under visible light irradiation. After only 2 hours of visible light irradiation, the degradation rate of tetracycline in water can reach 94.5%, and after 3 hours of visible light irradiation, the tetracycline in water is almost completely degraded.
[0028] The present invention stabilizes ethylene glycol (EG) around the copper-doped Bi2WO6 precursor by a dissolution-precipitation method, reduces the surface energy of nanoparticles through hydroxyl interactions, inhibits nanoparticle aggregation, and partially removes hydroxyl groups after high-temperature heat treatment to expose reaction centers. The introduction of copper atoms improves the energy band structure, which is conducive to the rapid separation of electron-hole pairs. The 0D nanostructure shortens the electron transfer distance, promotes the exposure of active centers, increases the specific surface area, promotes the adsorption and activation of O2, and significantly improves the rate of photocatalytic oxidation reaction.
[0029] The present invention reveals the role of 0D copper-doped nanomaterials in promoting carrier separation and O2 activation in photocatalytic oxidation reactions through characterizations such as photoluminescence spectroscopy (PL), electron spin resonance (ESR), and photocurrent response curves. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a transmission electron microscope image of the catalyst of Example 1.
[0031] Figure 2 This is an X-ray photoelectron spectroscopy (XPS) graph of the catalyst of Example 1.
[0032] Figure 3 This is the XPS graph of the catalyst of Example 1 corresponding to the Bi element.
[0033] Figure 4 This is the XPS graph of the catalyst of Example 1 corresponding to the Cu element.
[0034] Figure 5 This is the XPS graph of the catalyst in Example 1 corresponding to the W element.
[0035] Figure 6 This is the XRD spectrum of the catalyst in Example 1 before and after the cycle test.
[0036] Figure 7 This is an electron spin resonance image of the catalyst free radical capture experiment in Example 1.
[0037] Figure 8 The photocurrent response curves of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 are shown.
[0038] Fig. 9 The photoluminescence spectra of the catalysts of Example 1, Comparative Example 1 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0039] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0040] Embodiment 1
[0041] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0042] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Cu-BiNP-Pr.
[0043] (3) The precursor was heated at 300°C at a rate of 5°C min -1 Under the conditions of heating for 3h, zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Cu-BiNP.
[0044] Embodiment 2
[0045] (1) 5.76 g of bismuth nitrate·5H2O, 0.016 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0046] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.1Cu-BiNP-Pr.
[0047] (3) The precursor was heated at 300°C at a rate of 5°C min -1 Under the conditions of heating for 3h, zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.1Cu-BiNP.
[0048] Embodiment 3
[0049] (1) 5.53 g of bismuth nitrate·5H2O, 0.08 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0050] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.5Cu-BiNP-Pr.
[0051] (3) The precursor was heated at 300°C at a rate of 5°C min -1 Under the conditions of heating for 3h, zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.5Cu-BiNP.
[0052] Embodiment 4
[0053] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140°C for 15 h.
[0054] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Cu-BiNP-Pr(140).
[0055] (3) The precursor was heated at 300°C at a rate of 5°C min -1 After heating for 3 h under the conditions of , zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Cu-BiNP(140).
[0056] Embodiment 5
[0057] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 170°C for 15 h.
[0058] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Cu-BiNP-Pr(170).
[0059] (3) The precursor was heated at 300°C at a rate of 5°C min -1 After heating for 3 h under the conditions of , zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Cu-BiNP(170).
[0060] Embodiment 6
[0061] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180°C for 15 h.
[0062] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Cu-BiNP-Pr(180).
[0063] (3) The precursor was heated at 300°C at a rate of 5°C min -1 After heating for 3 h under the conditions of , zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Cu-BiNP(180).
[0064] Embodiment 7
[0065] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 20 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 140°C for 15 h.
[0066] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Cu-BiNP-Pr(20).
[0067] (3) The precursor was heated at 300°C at a rate of 5°C min -1 After heating for 3 h under the conditions of , zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Cu-BiNP(20).
[0068] Embodiment 8
[0069] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 12 h.
[0070] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Cu-BiNP-Pr(12).
[0071] (3) The precursor was heated at 300°C at a rate of 5°C min -1After heating for 3 h under the conditions of , zero-dimensional copper-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Cu-BiNP (12).
[0072] Comparative Example 1
[0073] (1) 5.82 g of bismuth nitrate·5H2O and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0074] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain BiNP-Pr.
[0075] (3) The precursor was heated at 300°C at a rate of 5°C min -1 By heating for 3 hours under the conditions of , copper-free bismuth tungstate zero-dimensional nanoparticles were obtained, namely the photocatalyst BiNP.
[0076] Comparative Example 2
[0077] (1) 1.61 g CuCL2 and 1.98 g Na2WO4·2H2O were added to 30 mL ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160 °C for 15 h.
[0078] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain CuNP-Pr.
[0079] (3) The precursor was heated at 300°C at a rate of 5°C min -1 After heating for 3 hours under the conditions of , copper tungstate zero-dimensional nanoparticles, namely the photocatalyst CuNP, were obtained.
[0080] Comparative Example 3
[0081] (1) First, 0.004 g CuO, 0.43 g WO3, and 1.0 g Bi2O3 were mixed in 20 ml ethanol and ultrasonically treated for 10 min.
[0082] (2) After evaporation, the catalyst was heated at 900°C for 12 h at a rate of 1 min / °C to obtain bulk copper-doped bismuth tungstate, i.e., the photocatalyst Bulk 0.3Cu-BiWO.
[0083] Comparative Example 4
[0084] (1) 5.65 g of bismuth nitrate·5H2O, 0.046 g of CoCl2, and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0085] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Co-BiNP-Pr.
[0086] (3) The precursor was heated at 300°C at a rate of 5°C min -1 Under the conditions of heating for 3h, zero-dimensional cobalt-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Co-BiNP.
[0087] Comparative Example 5
[0088] (1) 5.65 g of bismuth nitrate·5H2O, 0.049 g of ZnCl2 and 1.98 g of Na2WO4·2H2O were added to 30 mL of ethylene glycol and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0089] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with deionized water, and vacuum dried for 12 h to obtain the precursor 0.3Zn-BiNP-Pr.
[0090] (3) The precursor was heated at 300°C at a rate of 5°C min -1 Under the conditions of heating for 3h, zero-dimensional zinc-doped bismuth tungstate nanoparticles were obtained, namely the photocatalyst 0.3Zn-BiNP.
[0091] Comparative Example 6
[0092] (1) 5.65 g of bismuth nitrate·5H2O, 0.048 g of CuCl2, 1.98 g of Na2WO4·2H2O and 0.05 g of cetyltrimethylammonium bromide (CTAB) were added to 30 mL of water and stirred for 1 h. The suspension was then transferred to a 50 mL polytetrafluoroethylene-lined stainless steel autoclave and reacted at 160°C for 15 h.
[0093] (2) After cooling to room temperature, the solid was separated by filtration, washed three times with ethanol and deionized water, and vacuum dried for 12 hours to obtain copper-doped bismuth tungstate nanosheets, namely, the photocatalyst 0.3Cu-BiNs.
[0094] Characterization
[0095] The transmission electron microscope photo of the catalyst prepared in Example 1 is as follows: Figure 1As shown, it has a spherical primary particle structure and a lattice spacing of 0.274 nm, corresponding to the 002 crystal plane of bismuth tungstate.
[0096] The X-ray photoelectron spectroscopy (XPS) of the catalyst prepared in Example 1 is as follows: Figures 2 to 5 As shown, Bi, O, W, and Cu elements all have corresponding peaks in the XPS spectrum, indicating the successful synthesis of 0.3Cu-BiNP.
[0097] Test Example 1
[0098] Test object: The photocatalyst prepared in each embodiment and comparative example was applied to tetracycline photodegradation reaction, and the tetracycline degradation rate and first-order reaction kinetic constant were tested.
[0099] Test conditions: In the photocatalytic degradation experiment, 30 mg of photocatalyst was dispersed in 100 mL of tetracycline solution and reacted at room temperature under irradiation of a 300 W xenon lamp (PLSXE300D) with a UV cutoff filter (λ>420 nm). First, the solution was stirred in a dark environment for 30 minutes to reach adsorption-desorption equilibrium, and then the degradation reaction was carried out under light for 120 minutes. Before and after the reaction, 3 mL of the sample was taken out for centrifugation, and the absorbance was measured at about 350 nm by UV-Vis spectrophotometry. Based on this, the degradation rate of tetracycline and the first-order reaction kinetic constant were calculated.
[0100] Test results: Based on the measured absorbance data, the degradation rate of tetracycline was calculated, and the first-order reaction kinetic constant was further calculated. The results are shown in Table 1.
[0101] Table 1 Tetracycline degradation rate and first-order reaction kinetic constants
[0102] Photocatalyst TC degradation rate (%) <![CDATA[Kinetic constant K (min -1 )]]> Example 1 (0.3Cu-BiNP) 94.5 0.026 Example 2 (0.1Cu-BiNP) 85 0.012 Example 3 (0.5Cu-BiNP) 78 0.0091 Example 4 0.3Cu-BiNP-Pr(140) 94.4 0.025 Example 5 0.3Cu-BiNP (170) 94.2 0.024 Example 6 0.3Cu-BiNP (180) 94 0.023 Example 7 0.3Cu-BiNP (20) 94 0.023 Example 8 0.3Cu-BiNP (12) 94.1 0.024 Comparative Example 1 (BiNP) 52 0.0052 Comparative Example 2 (CuNP) 54 0.005 Comparative Example 3 (Bulk 0.3Cu-BiWO) 30 0.0018 Comparative Example 4 (0.3Co-BiNP) 71 0.0078 Comparative Example 5 (0.3Zn-BiNP) 60 0.0064 Comparative Example 6 (0.3Cu-BiNs) 39 0.0029
[0103] As shown in Table 1, the zero-dimensional copper-doped bismuth tungstate nanoparticle photocatalysts prepared in Examples 1 to 8 have excellent degradation capabilities for tetracycline under visible light conditions. After only 2 hours, the degradation rate of tetracycline generally reaches 80%, and the first-order reaction kinetic constant generally exceeds 0.01 min -1 In addition, factors such as the copper doping amount, reaction temperature, reaction time and solvent volume all affect the photocatalytic performance to varying degrees, among which the catalyst 0.3Cu-BiNP prepared in Example 1 exhibits the best tetracycline degradation performance under visible light conditions.
[0104] Comparing Example 1 and Comparative Example 1, in the absence of copper doping, the photocatalytic performance of bismuth tungstate zero-dimensional nanoparticles significantly decreased. This shows that copper doping plays a key role in improving the photocatalytic degradation efficiency of bismuth tungstate zero-dimensional nanoparticles of tetracycline. Copper doping may help to improve the separation efficiency of electron-hole pairs in the photocatalytic process of bismuth tungstate zero-dimensional nanoparticles, reduce recombination, and thus enhance the photocatalytic activity. Comparative Example 4 uses cobalt-doped bismuth tungstate zero-dimensional nanoparticles as a photocatalyst for degrading tetracycline, and Comparative Example 5 uses zinc-doped bismuth tungstate zero-dimensional nanoparticles as a photocatalyst for degrading tetracycline, but the catalytic effect is significantly lower than that of copper-doped bismuth tungstate zero-dimensional nanoparticles. The efficiency of photocatalytic degradation of tetracycline in Comparative Example 2 is also significantly reduced compared with Example 1, showing that in the absence of bismuth, the pure copper tungstate material has only weak photocatalytic performance. The above results show that copper doping in bismuth tungstate plays a vital role in constructing an effective visible light catalytic degradation system for tetracycline.
[0105] Comparative Example 3 shows the performance of bulk copper-doped bismuth tungstate, and its photocatalytic efficiency is much lower than that of Example 1. Comparative Example 6 shows the performance of copper-doped bismuth tungstate in nanosheet form, and its photocatalytic efficiency is also significantly lower than that of Example 1. This shows that nanoscale zero-dimensional copper-doped bismuth tungstate plays an important role in improving photocatalytic activity. In the photocatalytic process, this zero-dimensional nanostructure helps to shorten the distance of electron transfer, promote the exposure of active centers, increase the specific surface area, and promote the adsorption and activation of O2.
[0106] Test Example 2
[0107] Test object: The photocatalyst prepared in each example was applied to tetracycline photodegradation reaction to test its tetracycline degradation rate.
[0108] Test conditions: In the photocatalytic degradation experiment, 30 mg of photocatalyst was dispersed in 100 mL of tetracycline solution and reacted at room temperature under irradiation of a 300 W xenon lamp (PLSXE300D) with a UV cutoff filter (λ>420 nm). First, the solution was stirred in a dark environment for 30 minutes to reach adsorption-desorption equilibrium, and then the degradation reaction was carried out under light for 180 minutes. Before and after the reaction, 3 mL of the sample was taken out for centrifugation, and the absorbance was measured at about 350 nm by UV-Vis spectrophotometry. Based on this, the degradation rate of tetracycline was calculated.
[0109] Test results: Based on the measured absorbance data, the degradation rate of tetracycline was calculated. The results are shown in Table 2.
[0110] Table 2 Example Tetracycline Degradation Rate
[0111] Photocatalyst TC degradation rate (%) Example 1 (0.3Cu-BiNP) 99.9 Example 2 (0.1Cu-BiNP) 99 Example 3 (0.5Cu-BiNP) 98.8
[0112] The results in Table 2 show that when the irradiation time is increased by another 1 h, tetracycline in water can be almost completely degraded.
[0113] Test Example 3
[0114] Test object: The catalyst sample prepared in Example 1 was subjected to a stability test experiment.
[0115] Test conditions: The catalyst prepared in Example 1 was subjected to 5 rounds of photocatalytic tetracycline degradation cycle experiments to test the degradation rate of tetracycline in each round. At the same time, the 0.3Cu-BiNP recovered after the cycle test was subjected to XRD test.
[0116] Test results: The degradation rate of tetracycline in each round is shown in Table 3.
[0117] Table 3 Stability test
[0118] Cycle times TC degradation rate (%) 1 95 2 92 3 88 4 87 5 84
[0119] The test results are shown in Table 2. The zero-dimensional copper-doped bismuth tungstate nanoparticle photocatalyst still has a high photocatalytic activity after 5 rounds of photocatalytic TC degradation cycle experiments.
[0120] The XRD spectra of the catalyst recovered before and after the cycle test are shown in Figure 6 As shown in Figure 1, the peaks at 28.3°, 32.9°, 47.2°, 56.0°, and 58.6° correspond to the (131), (002), (202), (133), and (262) crystal planes, respectively. The characteristic peaks of the sample after the cycle test remain consistent with those before the test, indicating that the crystal form of the catalyst has not changed significantly after the cycle test.
[0121] Figure 7 This is an electron spin resonance image of a free radical capture experiment in Example 1. 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) was used as a capture agent. Superoxide radicals were successfully captured under light conditions, indicating that O2 was successfully activated. Figure 8 and Fig. 9 In the photocurrent test and photoluminescence spectrum, Example 1 showed the highest carrier separation degree and the lowest recombination rate, which proved that zero-dimensional copper-doped bismuth tungstate nanoparticles showed excellent charge separation ability and oxygen activation ability, and showed great potential in the field of antibiotic degradation represented by tetracycline.
[0122] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst, characterized in that: The following steps are involved: Step S1.1: using tungstate, bismuth salt and copper salt as raw materials, forming a suspension under the stabilization and dispersion effect of ethylene glycol; Step S1.2: placing the suspension formed in step S1.1 in a sealed container and heating it to obtain a nano-colloidal substance; Step S1.3: washing and drying the nano-colloid formed in step S1.2 to obtain a photocatalyst precursor; Step S1.4: heat-treating the photocatalyst precursor obtained in step S1.3 to obtain the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst.
2. The method for preparing the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst according to claim 1, characterized in that: In step S1.1, the tungstate is sodium tungstate, the bismuth salt is bismuth nitrate, and the copper salt is copper chloride.
3. The method for preparing the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst according to claim 1, characterized in that: In step S1.1, 5.53-5.76 parts by mass of Bi(NO3)3•5H2O, 0.016-0.08 parts by mass of CuCl2, and 1.70-2.20 parts by mass of Na2WO4•2H2O are added to 22.2-33.3 parts by mass of ethylene glycol and mixed to form a suspension.
4. The method for preparing the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst according to claim 3, characterized in that: In step S1.2, the suspension formed in step S1.1 is placed in a high-pressure sealed container and reacted at 140-180° C. for 12-15 h to form a nano-colloid.
5. The method for preparing the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst according to claim 4, characterized in that: In step S1.3, the nano-colloid is filtered to separate the solid, which is washed with deionized water and vacuum dried to obtain a photocatalyst precursor.
6. The method for preparing the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst according to claim 5, characterized in that: In step S1.4, the precursor is heated to 300±5°C at a heating rate of 5±1°C / min, heated for 2-5 hours under this condition, and then cooled to room temperature to obtain the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst.
7. A visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst, characterized by: Prepared according to the preparation method according to any one of claims 1 to 7.
8. A method for treating tetracycline wastewater, characterized in that: The following steps are involved: Step S2.1: dispersing the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst described in claim 7 into the wastewater containing tetracycline to be treated to obtain a mixed solution; Step S2.2: subjecting the mixed solution obtained in step S2.1 to a photocatalytic reaction under visible light irradiation to degrade tetracycline in the sewage; Step S2.3: After the reaction is completed, the photocatalyst is separated from the mixed liquid to obtain purified water.
9. The method for treating tetracycline wastewater according to claim 8, characterized in that: In step S2.3, the photocatalyst is recovered from the mixed solution by filtration or centrifugation.
10. The method for treating tetracycline wastewater according to claim 8, characterized in that: In step S2.1, the sewage to be treated contains a variety of organic pollutants including tetracycline; the photocatalyst added to the sewage to be treated is a composite photocatalyst including the visible light responsive zero-dimensional copper-doped bismuth tungstate nanophotocatalyst described in claim 7.
